2009
DOI: 10.1182/blood-2008-06-161075
|View full text |Cite
|
Sign up to set email alerts
|

Role of GM-CSF signaling in cell-based tumor immunization

Abstract: Granulocyte-macrophage colonystimulating factor (GM-CSF) is a potent adjuvant in cancer vaccination; however, the specific role of endogenous GM-CSF remains unknown. We performed cellbased vaccination in 2 tumor models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 48 publications
(57 reference statements)
3
29
0
1
Order By: Relevance
“…Many studies have outlined the beneficial effects of probiotics on various aliments such as food allergies (Kalliomäki and Isolauri, 2003), inflammatory bowel disease, and ulcerative colitis (Stephani et al, 2011). Probiotics exert their modulatory actions by different mechanisms, including: anti-genotoxicity; inhibition of colonic enzyme activity, which reduces the harmful effects of carcinogens activated by enzymatic action in the colon (Liong, 2008); control of the growth of potentially harmful bacteria (Zarei et al, 2009); interaction with colonocytes; and enhancement of homeostasis and the integrity of the epithelial barrier. Recently, research by Hijová et al (2012) on colon cancer rats has indicated that prebiotics have a protective effect and may be useful for colon cancer prevention and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have outlined the beneficial effects of probiotics on various aliments such as food allergies (Kalliomäki and Isolauri, 2003), inflammatory bowel disease, and ulcerative colitis (Stephani et al, 2011). Probiotics exert their modulatory actions by different mechanisms, including: anti-genotoxicity; inhibition of colonic enzyme activity, which reduces the harmful effects of carcinogens activated by enzymatic action in the colon (Liong, 2008); control of the growth of potentially harmful bacteria (Zarei et al, 2009); interaction with colonocytes; and enhancement of homeostasis and the integrity of the epithelial barrier. Recently, research by Hijová et al (2012) on colon cancer rats has indicated that prebiotics have a protective effect and may be useful for colon cancer prevention and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Among all adjuvants, toll-like receptor (TLR) agonists and cytokines including GM-CSF have been tested in both preclinical and clinical settings for cancer treatment. 8,9 However, some adjuvants may have tumor-promoting effects, for example, TLR4 ligation enhances immunosuppressive cytokine production by human lung cancer cells. 10 High dose of GM-CSF has been shown to chemoattract MDSCs thus dampening the efficacy of cancer vaccines.…”
mentioning
confidence: 99%
“…Despite a body of literature that supports use of GM-CSF as a vaccine adjuvant [4, 39, 40], two prospective randomized phase II trials have shown negative effects of GM-CSF in combination with other vaccine adjuvants [21, 41]. The overall CTL response rates (43 and 47% in Arms A and B) are based on ELIspot assays performed after in vitro stimulation; which has been required for other studies when GM-CSF was used in the adjuvant [4, 20, 21]; we expect that the magnitude of these responses would be greater using IFA without GM-CSF.…”
Section: Discussionmentioning
confidence: 99%